Trends in Western Popular Music : Analyzing Top Album Charts and Online User Opinions - Vuorinen, Heikki (My University, 2024)
During recent years, music has become an increasingly larger part of our lives due to the vast availability of music online. Technological innovations have always played a key role in the music industry, changing the ways music is recorded, distributed and consumed. However, not everyone agrees that these changes have improved the quality of music and it's quite common among music enthusiasts to hear the phrase "Music was better before". Of course, the perception of music is highly subjective, but it's possible to examine the changes that could lead consumers to have this view. In this thesis our goal is to examine how the technological evolution of music distribution has affected the trends and dynamics of music consumption, based on historical Billboard 200 charts, which represent the weekly 200 best selling albums in the US. Our goal was to evaluate topics such as the amount of yearly unique albums, the popularity of genres and the current Rate Your Music user ratings of past and contemporary albums. We found that the popularity of the CD format led to an increase in unique album appearances in the list up until around the time streaming started gaining popularity. The popularity of streaming also led to an increase in the sales of older records, which could now be monetized through streaming services. Additionally, we visualized the genre popularity over time and examined the online user based album ratings regarding time and genres. We found that the overall average user ratings decreased during the late 1990s, and that there are significant differences in the way ratings are distributed accross genres, most notably rock being the highest rated with an average of 3.39 stars on a scale from 1 to 5 stars, and hip hop the lowest with 2.90/5 stars average.
Keywords: Billboard 200, Popular Music, Music Trends, Music Industry Dynamics, Rate Your Music, Music Genre Trends, Music Streaming